Anti-ribosomal P protein antibodies detected by immunoblotting in patients with connective tissue diseases: their specificity for SLE and association with IgG anticardiolipin antibodies. Issue 12 (1st December 2000) - Ghirardello, A; Doria, A; Zampieri, S; Gerli, R; Rapizzi, E; Gambari, P F
Abstract : OBJECTIVE: To assess the prevalence and clinical and serological associations of anti-ribosomal P protein antibodies (anti-P antibodies) in patients with connective tissue diseases (CTDs) and investigate the immunobiological nature of autoantibody clustering in which anti-P antibodies play a part. METHODS: IgG anti-P antibodies in the sera of 267 patients with CTDs and 31 healthy subjects were analysed by immunoblotting performed on cytoplasmic extract of Raji cells. 60 patients with systemic lupus erythematosus (SLE), 32 systemic sclerosis, 46 primary Sjögren's syndrome, 16 poly/dermatomyositis, 11 rheumatoid arthritis, 8 undifferentiated CTD, 72 overlap CTD, and 22 primary antiphospholipid syndrome were studied. Anti-P antibodies were affinity purified by elution from nitrocellulose bound antigen and tested by ELISA for their binding activity to cardiolipin. RESULTS: Anti-P antibodies were detected in 16 (6%) patients and in none of the controls: 12/60 SLE (20%) and 4/80 undifferentiated/overlap patients with CTD (5%). A close association of IgG antibodies with P proteins and with cardiolipin was seen in lupus sera (p=0.0009, odds ratio 18.33). Anti-P antibodies from 9 of 12 anti-P lupus serum samples could be affinity purified and none of the affinity purified fractions cross reacted with ELISA plate coated cardiolipin. CONCLUSIONS: Anti-P immunoreactivity is a specific marker of SLE and lupus-like disease and its detection is recommended as a powerful diagnostic tool. Anti-P antibodies are strongly clustered with IgG anticardiolipin antibodies in lupus sera, even if they are independently elicited. This suggests that their cognate autoantigens play a part in a common pathogenetic pathway in SLE.